Value added and business feasibility analysis of chili sauce products in Banggae District, Majene Regency - Putri, Dwi Ahrisa; Kaimuddin, Kaimuddin; Mas’udin, Gita Afmiranti (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2022)
SMEs are expected to grow and compete in products development that have value added to encourage economic sustainability. The value added provided a value to maintaining and enhancing the quality of agricultural products can also add to its economic value by processing it into a product such as chili sauce products. This study aims to find out how much value added is given and the value of business feasibility. The research sample was determined deliberately with the consideration of choosing the entire chili sauce business unit as many as 7 SMEs in Banggae District, Majene Regency which processes chili sauce and has fresh chili mixture ingredients. The data analysis used is a value-added analysis of the estimated value added of the product, labor rewards, rewards for capital and management while the R /C ratio is to see the profit of a business to the costs used and to find out whether the business is feasible. The results showed that there is a value added provided from chili processing in one production is Rp. 356,776.7 / kg so that it can increase the difference between the input price and the selling price of the output which indicates that processing chili into a product can be of high value. The chili sauce business has been efficient because the R /C ratio value of more than one, which is 1.63, means that it can be concluded that this business feasible to be developed.